Pasoa: Komunikasi Budaya Masyarakat Negeri Mamala, Kecamatan Leihitu, Kabupaten Maluku Tengah - Fitriyani, Andi; Putuhena, M. Ihwan F.; Ren'el, Baiti (Dimar Jaya Publishing, 2024)
This study examines how cultural communication of Pasoa within the Negeri Mamala community, Leihitu Sub-district, Central Maluku Regency, Maluku Province. This research utilizes a qualitative research method with an ethnographic approach. The results of the study illustrate that; 1) Pasoa cultural communication within the Negeri Mamala community is a form of symbolization of cultural life carried out for important things to be discussed in the same family line. 2) Pasoa communication as a tradition of the Negeri Mamala community has remained carried out until today, especially in particular events or activities. 3). Pasoa communication is a hereditary tradition in conveying messages from one family to the other communities maintained by the Negeri Mamala community.